Synthesis of fused tricyclic systems by thermal Cope rearrangement of furan-substituted vinyl cyclopropanes. Issue 21 (15th May 2018) - Klaus, Verena; Wittmann, Stéphane; Senn, Hans M.; Clark, J. Stephen
Abstract : A novel method for the construction of hexahydroazuleno[4, 5- b ]furans has been developed in which 1-furanyl-2-alkenylcyclopropanes undergo highly stereoselective thermal Cope rearrangement. Abstract : A novel method for the stereoselective construction of hexahydroazuleno[4, 5- b ]furans from simple precursors has been developed. The route involves the use of our recently developed Brønsted acid catalysed cyclisation reaction of acyclic ynenones to prepare fused 1-furanyl-2-alkenylcyclopropanes that undergo highly stereoselective thermal Cope rearrangement to produce fused tricyclic products. Substrates possessing an E -alkene undergo smooth Cope rearrangement at 40 °C, whereas the corresponding Z -isomers do not react at this temperature. Computational studies have been performed to explain the difference in behaviour of the E - and Z -isomers in the Cope rearrangement reaction. The hexahydroazuleno[4, 5- b ]furans produced by Cope rearrangement have potential as advanced intermediates for the synthesis of members of the guaianolide family of natural products.